The Effects of Peppermint Oil on Nausea, Vomiting and Retching in Cancer Patients Undergoing Chemotherapy: An Open Label Quasi-Randomized Controlled Pilot Study - Nuriye Efe Ertürk; Sultan Taşcı (Elsevier, 2021)
Objectives: The current study evaluated the effects of peppermint oil on the frequency of nausea, vomiting, retching, and the severity of nausea in cancer patients undergoing chemotherapy. Design: A quasi-randomized controlled study. Setting: Patients were recruited from the ambulatory chemotherapy unit of a public hospital located (Batman, Turkey) between September 2017 and September 2018. Interventions: The participants in the intervention group applied one drop the aromatic mixture on the spot between their upper lip and their nose, three times a day for the five days following chemotherapy administration, in addition to the routine antiemetic treatment. Participants in the control group underwent only the routine antiemetic treatment. Main outcome measures VAS-the severity of nausea and the Index of Nausea, Vomiting, and Retching. Results: The VAS nausea score was significantly lower after peppermint oil applying in the patients receiving Folfirinox (treatment effect (mean dif.): 4.00±2.28; P<0.001), Paclitaxel-Trastuzumab (treatment effect (mean dif.): 1.70±0.90; P=0.014), Carboplatin-Paclitaxel (treatment effect (mean dif.): 3.71±1.41; P<0.001), and Cyclophosphamide-Adriamycin (treatment effect (mean dif.): 1.41±0.73; P=0.005) excluding cisplatin scedule (treatment effect (mean dif.): 0.56±2,18; P=0.642). We detected a statistical significant difference in the change in frequency of nausea, vomiting, retching in the other all schedules excluding cisplatin schedule (P<0.05). Conclusions: The peppermint oil was significantly reduced the frequency of nausea, vomiting, retching and the severity of nausea in cancer patients undergoing chemotherapy. Therefore, usage of peppermint oil together with antiemetics after chemotherapy with moderate and low emetic risk may be recommended to cope with CINV.